ANALISIS PENENTUAN HARGA POKOK PRODUKSI PADA USAHA KECIL MENENGAH SENTRA PENGRAJIN BAMBU PADA UKM WAHANA BAMBU WILLIS GUNUNG SARI LOMBOK BARAT - Cinthya, Luh Nyoman; Larasanty, Larasanty; Animah, Animah; Isnawati, Isnawati (Jurnal Ilmiah Akuntansi Indonesia, 2019)
The aim of this study was to determine (1) Calculation of the goods manufactured cost at SMEs, (2) Calculation of the goods manufactured cost based on full costing methods at SMEs ds manufactured cost supposed to be based on activity based costing system at SMEs,(3) Calculation of the goo and (4) Comparison of the goods manufactured cost based on SMEs calculation, full costing methods, and activity based costing system. This was a case study research at ?Wahana Bambu Wilis? located in Dasan Bara Hamlet, Taman Sari Village. The study results showed that the goods production cost per unit based on SMEs calculation was IDR 4,043,000 for bamboo berugak, IDR 683,226 for chair, IDR 300,246 for lazy cots, IDR 238,040 for shelves, and IDR 125,500 for bedek. Based on full costing methods, the calculation results was IDR 4,047,473 for bamboo berugak, IDR 699,165 for chair, IDR 316,271 for lazy cots, IDR 253,979 for shelves, and IDR 142,552 for bedek. Whereas with activity based costing system calculation cost of goods manufactured per unit was IDR 4,103,175 for bamboo berugak, IDR 709,598 for chair, IDR 302,759 for lazy cots, IDR 200,132 for shelves, and IDR 117,716 for bedek. The cost of goods manufactured calculated by SMEs was lower than the full costing methods. When compared with the activity based costing, there was an undercosting for SMEs, whereas the cost of goods manufactured was lower than activity based costing for bamboo berugak, chair and lazy cots with cost difference amounting IDR 60,175; IDR 26,372 and IDR 2,513. Cost of goods manufactured for shelves and bedek based on SMEs calculation was higher than activity based costing system that results on overcosting with cost difference amounting IDR 37,908 and IDR 7,784.